3D Printing of Self‐Organizing Structural Elements for Advanced Functional Structures. Issue 5 (16th April 2018) - Chi, Jinchun; Zocca, Andrea; Agea‐Blanco, Boris; Melcher, Jörg; Sparenberg, Marc; Günster, Jens
Abstract: A shape evolution approach based on the thermally activated self‐organization of 3D printed parts into minimal surface area structures is presented. With this strategy, the present communication opposes currently established additive manufacturing strategies aiming to stipulate each individual volumetric element (voxel) of a part. Instead, a 3D structure is roughly defined in a 3D printing process, with all its advantages, and an externally triggered self‐organization allows the formation of structural elements with a definition greatly exceeding the volumetric resolution of the printing process. For enabling the self‐organization of printed objects by viscous flow of material, functionally graded structures are printed as rigid frame and melting filler. This approach uniquely combines the freedom in design, provided by 3D printing, with the mathematical formulation of minimal surface structures and the knowledge of the physical potentials governing self‐organization, to overcome the paradigm which strictly correlates the geometrical definition of 3D printed parts to the volumetric resolution of the printing process. Moreover, a transient liquid phase allows local programming of functionalities, such as the alignment of functional particles, by means of electric or magnetic fields. Abstract : An approach based on the thermally activated self‐organization of 3D printed parts into minimal surface structures is presented, which opposes currently established additive manufacturing strategies aiming to stipulate each individual volumetric element of a part. Instead, a 3D structure is printed and subsequent self‐organization allows formation of structural elements which definition greatly exceeds the volumetric resolution of the printing process.